Short and long term evaluations of public employment services in Italy - Naticchioni, Paolo; Loriga, Silvia (Louvain-la Neuve, 2008)
"In this paper we evaluate the efficacy of Public Employment Services in Italy (PESs) in increasing the unemployment to employment transition probabilities, through matching techniques. Exploiting the longitudinal dimension of the LFS data we design an evaluation structure that allows observing outcomes in both the short (at most 3 months) and the long run (at most 12 and 15 months). In this framework, PES users show a lower probability of finding a job in the short term, because of a lock-in effect, while in the long term this probability turns out to be positive. Similar results are derived when considering as outcome a proxy for the quality of the job, i.e. having found a permanent job. Robustness checks and sensitivity analysis confirm this evidence, suggesting also that our estimates are to be considered as lower bound in the eventuality of unobserved negative selection into treatment."